PROBLEMY WYDZIELANIA PERYFERII SPOŁECZNO-GOSPODARCZYCH - Bajerski, Artur (Wydział Prawa i Administracji UAM, 2008)
“Periphery” is a multi-dimensional notion. The basic dimensions include geographical, economic and social (socio-cultural). The geographical aspect of a periphery is basically limited to its location relative to a centre. The economic and social dimensions, although focusing on economic and social characteristics, also rely on the location relative to a centre, as exemplified by the delimitation of a periphery in economic terms through its location outside the zone of the greatest economic activity. Because economic and social dimensions are wider and more complex than the geographical one, they constitute higher-order dimensions. Assuming socio-economic properties as the only criteria for the delimitation of a periphery is insufficient because the key element o f this notion is distance from a core. Usually, however, the location (distance) aspect tends to be ignored. One reason may be the popularity of this term which leads to its intuitive use. Another is the fact that the inclusion o f distance into the procedure of periphery delimitation is rather troublesome because it involves the knowledge of the effect that the distance from the centre has on the socio-economic situation. The distance aspect, however, can be ignored in the case of a borderland. Therefore, peripherality can be defined by purely socio-economic variables. The division into a core and a periphery is usually dichotomous, i.e. one where an area is classified either as a core or as a periphery. An advantage of the dichotomy is its simplicity, and a drawback, lack of intermediate categories. An opposite o f a dichotomous division is the conception of a continuum, but it would be too unwieldy to use since the number o f classes distinguished would equal the number o f units analysed. Thus, the right approach seems to be the delimitation of several classes of peripherality as this would facilitate an analysis and the readability of its results. Moreover, it gives more emphasis to the intermediate categories, which also become part of the study. The construction of multi-class divisions, however, involves the use of “hard” data, mainly socio-economic, which may lead to a periphery appearing somewhat “de-socialised” and “de-cultured”. The notion of a periphery and the research procedure aiming at its identification need some revitalisation which should embrace not only the inclusion o f distance from the centre and a departure from the centre-periphery dichotomy in favour of multi-class divisions, but also the working out of indicators defining peripherality.
PROBLEMS WITH DELIMITATION OF SOCIO-ECONOMIC PERIPHERIES